Solo leveling. 10 - Ch'ugong; h-goon (Anime creator) (Ize Press, 2024)
"Saving Japan from total destruction at the hands of the King of Giants earns Jinwoo and Ahjin Guild world-wide recognition and a spot at the International Guild Conference. But heading to America means crossing paths with Dongsoo Hwang, who has a bone to pick with Jinwoo about the death of his brother--and isn't above using Jinho as bait!"--Amazon.